Particle track structure measurements from 0.5 to 18 nm in nitrogen using the Jet Counter nanodosemeter. (July 2020) - Bancer, Aleksandr; Pietrzak, Marcin; Mietelska, Monika
Abstract: Experimental nanodosimetry aims at establishing a new concept of radiation quality that builds on measurable characteristics of the particle track structure at the nanometre scale. This article presents the capabilities and limits of the Jet Counter nanodosemeter for the whole range of experimentally available targets' sizes. The Jet Counter device can be used for reliable measurements of ionisation cluster-size distributions for target sizes ranging from 1 to 16 nm in nitrogen. Measurements outside this range have also been performed, but their reliability has yet to be proven. Highlights: The Jet Counter nanodosemeter was tested in wide range of size of nitrogen targets. The Jet Counter proved to be a reliable device for track-structure measurements. The device and results presented can be used as reference for Monte Carlo codes.